IMPLEMENTASI MODEL PEMBELAJARAN THINK TALK WRITE (TTW) UNTUK MENINGKATKAN KEMAMPUAN DISPOSISI MATEMATIS SISWA [IMPLEMENTATION OF THINK TALK WRITE (TTW) LEARNING MODEL TO IMPROVE STUDENTS' MATHEMATICAL DISPOSITION ABILITY] - Mahmudati, Rina (Polyglot, 2023)
AbstractThe quality of the nation's life is reflected in the quality of education which includes mathematical abilities, one of which is mathematical soft skills, namely mathematical disposition. The purpose of this study is to describe the implementation of the TTW learning model to improve the mathematical disposition of students at SDN 2 Banyukembar which is the target school of the Class 4 Teaching Campus Program. This classroom action research was conducted in August-October 2022 in two cycles with each cycle consisting of 5 meetings. The results of this study indicate that the implementation of the TTW learning model in mathematics learning has increased students' mathematical disposition abilities, which is indicated by an increase in the achievement of students' mathematical disposition abilities by 71.4% at the end of the second cycle.Bahasa Indonesia Abstrak Kualitas kehidupan bangsa tercermin dari kualitas pendidikan yang didalamnya memuat kemampuan matematis, salah satunya softskill bermatematika adalah disposisi matematis. Tujuan penelitian ini adalah mendeskripsikan implementasi model pembelajaran TTW untuk meningkatkan kemampuan disposisi matematis siswa SDN 2 Banyukembar yang merupakan sekolah sasaran Program Kampus Mengajar Angkatan 4. Penelitian tindakan kelas ini dilakukan Agustus-Oktober 2022 dalam dua siklus dengan masing-masing siklus terdiri dari 5 pertemuan. Hasil penelitian ini menunjukkan bahwa implementasi model pembelajaran TTW pada pembelajaran matematika telah meningkatkan kemampuan disposisi matematis siswa yang ditunjukkan dengan adanya peningkatan capaian kemampuan disposisi matematis siswa sebesar 71,4% di akhir siklus II.